2022
DOI: 10.1177/08404704211062575
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing virtual care: Bridging the healthcare system and citizen silos to create an integrated future

Abstract: The pandemic has accelerated the move to virtual care. This has included remote monitoring and implementation of technologies that allow for patient care at home and assisted living for ageing in place. Technologies are available to help consumers to maintain their health and wellness. However, challenges associated with implementing virtual care remain. In this article, we describe some of these challenges, along with the need to develop new models for promoting effective and sustainable virtual care. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Thus, the optimization of limited resources in hospitals becomes possible through hospital@home care models (26). A cost-intensive hospital infrastructure can be reduced using hospital@home or the patient's own technologies could be integrated into a hospital@home model to reduce costs (56). This is the case as more and more individuals are buying consumer technologies to support aging in the home.…”
Section: Strengths Weaknesses Opportunities and Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the optimization of limited resources in hospitals becomes possible through hospital@home care models (26). A cost-intensive hospital infrastructure can be reduced using hospital@home or the patient's own technologies could be integrated into a hospital@home model to reduce costs (56). This is the case as more and more individuals are buying consumer technologies to support aging in the home.…”
Section: Strengths Weaknesses Opportunities and Threatsmentioning
confidence: 99%
“…Integration of the individual digital ecosystem with the institutional digital health ecosystem would be beneficial (56). Thus far, the healthcare technology infrastructures are still siloed and disconnected.…”
Section: Practical and Research Implicationsmentioning
confidence: 99%
“…technology-induced errors) emerged. 6 , 10 Researchers identified that as we introduce new technologies, we now need to recognize the following: (1) technology is part of a digital health ecosystem 15 ; (2) technology leads to the creation of new healthcare processes that can introduce new types of errors (i.e. technology-induced errors) (see Table 1 ); and (3) technology-induced errors can propagate throughout a digital health ecosystem (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The IOM identified that “safe implementation of health IT is a complex, dynamic process that requires a shared responsibility between vendors and healthcare organizations.” 4 Today, healthcare has become even more complex with a growing number of new technologies aimed at healthcare consumers and health organizations coming to market. 15 In addition to this, health technologies (software, hardware, and medical devices) are increasingly becoming integrated across the healthcare system providing data and information that needs to be understood by health professionals and citizens so that effective health decisions are made (via devices such as phones and wearable sensors). 15 - 20 Today’s healthcare system is highly dependent on technology for its effectiveness, efficiency, and safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation